Pre-Service Science Teachers' Perception About High Order Thinking Skills (HOTS) in the 21st Century - Afandi Afandi; Sajidan Sajidan; Muhammad Akhyar; Nunuk Suryani (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2018)
In the 21st century, the pre-service science teachers faced on extremely global competitiveness, globalization, technologically driven by information and rapidly media-saturated that needs appropriate skills to meet these challenges. The aims of this study is to identify pre-service science teacher perception about high order thinking skills (HOTs) in 21st century. This study employed quantitative design using a survey research method involved 120 pre-service science teachers from Tanjungpura University. The results of this study indicated that prospective science teachers have an awareness of the importance of HOTs and their also knowing that the learning do emphasized on the aspects of HOTs is essential to face the challenges of the 21st century. It is indicated by the mean score of pre-service science teacher perception about the important of HOTs to meet the challenges in the 21st century (M = 4.29, SD = 0.61) and the skills of HOT that their will be required to becomes a teacher in the 21st century (M = 4.31; SD = 0.47) in the high level. This result provides the reasons why we need cultivating a positive awareness of the importance of HOTs in order to fostering the need for teaching that emphasizes the aspects of HOTs during pre-service education.